Effects of aeration position on organics, nitrogen and phosphorus removal in combined oxidation pond–constructed wetland systems. (December 2015) - Wang, Xiaoou; Tian, Yimei; Zhao, Xinhua; Peng, Sen; Wu, Qing; Yan, Lijian
Highlights: Aeration position (AP) had significant effects on DO distribution in aerated CWs. AP imposed significant effects on organics and nitrogen removal in aerated CWs. Neither artificial aeration nor AP had significant influence on TP removal in CWs. This study offers a reference for the design of aerated CWs. Abstract: Given that few studies investigated the effects of aeration position (AP) on the performance of aerated constructed wetlands, the aim of this study was to evaluate the effects of AP on organics, nitrogen and phosphorus removal in lab-scale combined oxidation pond–constructed wetland (OP–CW) systems. Results showed that middle aeration allowed the CW to possess more uniform oxygen distribution and to achieve greater removals of COD and NH3 -N, while the CW under bottom aeration and surface aeration demonstrated more distinct stratification of oxygen distribution and surface aeration brought about better TN removal capacity for the OP–CW system. However, no significant influence of artificial aeration or AP on TP removal was observed. Overall, AP could significantly affect the spatial distribution of dissolved oxygen by influencing the oxygen diffusion paths in aerated CWs, thereby influencing the removal of pollutants, especially organics and nitrogen, which offers a reference for the design of aerated CWs.